Hubungan Pelayanan Informasi Obat dengan Pengetahuan dan Tingkat Kepatuhan Pasien Hipertensi di Puskesmas Kerang Kecamatan Batu Engau: The Relationship between Drug Information Services and the Knowledge and Level of Compliance of Hypertension Patients at the Kerang Community Health Center, Batu Engau District - Dayuh Anggun Mandalika; Herman Herman; Nisa Naspiah (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
The World Health Organization (WHO) states that hypertension is an increase in systolic pressure greater than or equal to 160 mmHg and/or diastolic pressure equal to or greater than 95 mmHg. According to data obtained from the Kerang health center for the 2022-2023 period, the total prevalence at the health center was 5,393 with a total population of 12,902. One way to overcome hypertension is to increase patient knowledge and compliance with treatment by providing Drug Information Services. The aim of this research is to determine the characteristics, knowledge and level of compliance, determine drug information services and determine the relationship between drug information services and the knowledge and level of compliance of hypertensive patients. The method used is observational analysis with data collection using a prospective approach using medical record data and interview results. The results of the research on the characteristics of the majority of patients were in the late adult phase, 25.4%, 70.1% were female, 59.7% had elementary school education and 64% worked as housewives. The level of compliance of hypertensive patients is still low with a percentage of 59.80% and the level of knowledge of hypertensive patients is also in the low category with a percentage of 52.24%. Drug information services that are often provided only include the name of the drug, preparation, dosage, how to use, storage and side effects. and a significant value was obtained for the Knowledge Level with a correlation value of 0.344 and the Compliance Level with a correlation value of 0.649. Keywords: Hypertension; Drug Information Services; Compliance and Knowledge Abstrak Salah satu cara untuk menanggulangi hipertensi adalah meningkatkan pengetahuan dan kepatuhan pasien dalam pengobatan dengan cara pemberian Pelayanan Informasi Obat. Tujuan penelitian ini untuk mengetahui karakteristik, pengetahuan dan tingkat kepatuhan, mengetahui pelayanan informasi obat serta mengetahui hubungan pelayanan informasi obat dengan pengetahuan dan tingkat kepatuhan pasien hipertensi. Metode yang digunakan adalah observasional analisis dengan pengambilan data secara pendekatan prospektif menggunakan data rekam medik dan hasil wawancara. Hasil penelitian karakteristik pasien mayoritas masuk fase dewasa akhir sebesar 25,4%, berjenis kelamin perempuan sebesar 70,1%, berpendidikan SD sebesar 59,7% dan berprofesi sebagai IRT sebanyak 64%. Tingkat kepatuhan pasien hipertensi masih rendah dengan presentase 59,80% dan tingkat pengetahuan pasien hipertensi juga termasuk kategori rendah dengan presentase 52,24%, pelayanan informasi obat yang sering diberikan hanya nama obat, sediaan, dosis, cara pakai, penyimpanan, dan efek samping dan diperoleh nilai signifikan pada Tingkat Pengetahuan nilai korelasi sebesar 0,344 dan Tingkat Kepatuhan dengan nilai korelasi sebesar 0,649. Kata Kunci: Hipertensi; Pelayanan Informasi Obat;Kepatuhan dan Pengetahuan